2021
DOI: 10.1289/ehp7351
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Blood Lead Levels and Coronary Artery Stenosis Measured Using Coronary Computed Tomography Angiography

Abstract: Background: Lead exposure is a risk factor for increased blood pressure and cardiovascular disease, even when blood lead levels (BLLs) are within the normal range. Objective: This study aimed to investigate the association between BLL and coronary artery stenosis (CAS) in asymptomatic adults using 128-slice dual-source coronary computed tomography (CT) angiography. Methods: We analyzed medical records data from 2,193 adults (1,461 men and 732… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Moderate to severe coronary artery stenosis was significantly associated with BLLs, with an adjusted OR for a 1 µg/dL increase in BLL of 1.14 ( P = 0.017). 22 In our study, it was confirmed that the relationship between the prevalence of CAC, CACS, and BLL was significant before and after adjusting for confounders. This will be sufficient evidence to support the conclusions presented in many studies on the relationship between lead exposure and CVD.…”
Section: Discussionsupporting
confidence: 79%
“…Moderate to severe coronary artery stenosis was significantly associated with BLLs, with an adjusted OR for a 1 µg/dL increase in BLL of 1.14 ( P = 0.017). 22 In our study, it was confirmed that the relationship between the prevalence of CAC, CACS, and BLL was significant before and after adjusting for confounders. This will be sufficient evidence to support the conclusions presented in many studies on the relationship between lead exposure and CVD.…”
Section: Discussionsupporting
confidence: 79%
“…However, they used CT‐angiography to examine the complexity of coronary artery stenosis rather than angiography, which is the golden standard. In addition, they did not exclude the family history of cardiovascular disorders (Kim et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly focused on the discussion of the risk factors of CAS in the general population and the elderly population. 22,23 This study investigated risk factors for early onset CAS and found that ALDH2 rs671 A/A genotype, overweight, smoking history, and diabetes mellitus were independent risk factors for early onset CAS. SNP rs671 is the main polymorphic site of ALDH2 gene, which is related to the enzyme activity of ALDH2.…”
Section: Discussionmentioning
confidence: 99%